2011
DOI: 10.1158/1078-0432.ccr-10-2276
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Correlates of NRAS and BRAF Mutations in Primary Human Melanoma

Abstract: Purpose: NRAS and BRAF mutations are common in cutaneous melanomas, although rarely detected mutually in the same tumor. Distinct clinical correlates of these mutations have not been described, despite in vitro data suggesting enhanced oncogenic effects. This study was designed to test the hypothesis that primary human cutaneous melanomas harboring mutations in NRAS or BRAF display a more aggressive clinical phenotype than tumors wild type at both loci.Experimental Design: Microdissection of 223 primary melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
219
7
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(274 citation statements)
references
References 13 publications
35
219
7
13
Order By: Relevance
“…Age-specific incidence patterns display early-and late-onset peak frequencies for trunk and face/ear melanomas, respectively [130,131], consistent with hypotheses that melanoma arises from more than one causal pathway and contain distinct melanoma genotypes [241]. NRAS and BRAF mutations, mutually exclusive of each other, are found, respectively, in 10-30 and 25-60 % of primary melanomas [60,63,64,93,228]. Less frequently, melanomas contain KIT mutations, particularly mucosal melanoma or melanomas arising on acral or on sun-damaged sites [53].…”
Section: Somatic Genetic Factors: Tumor Subtypessupporting
confidence: 64%
See 1 more Smart Citation
“…Age-specific incidence patterns display early-and late-onset peak frequencies for trunk and face/ear melanomas, respectively [130,131], consistent with hypotheses that melanoma arises from more than one causal pathway and contain distinct melanoma genotypes [241]. NRAS and BRAF mutations, mutually exclusive of each other, are found, respectively, in 10-30 and 25-60 % of primary melanomas [60,63,64,93,228]. Less frequently, melanomas contain KIT mutations, particularly mucosal melanoma or melanomas arising on acral or on sun-damaged sites [53].…”
Section: Somatic Genetic Factors: Tumor Subtypessupporting
confidence: 64%
“…BRAF-mutant melanomas are associated with young age at diagnosis, intermittently sun-exposed sites such as the trunk, superficial spreading subtype, absence of solar elastosis, and presence of mitoses [17,60,63,64,93,144,155,228]. NRAS-mutant melanomas are associated with older age at diagnosis, but less associated with specific anatomic location, are more likely to be nodular subtype, and show increased Breslow thickness and presence of mitoses [60,63,64,86,139,228,231,234].…”
Section: Clinical Characteristics Of Tumor Subtypesmentioning
confidence: 99%
“…Ulceration was reported to be lower in NRAS-mutated tumors in comparison to BRAF mutated tumors (9.7 versus 22.4%, respectively) [63] but no obvious effect of mutational status on the presence of ulceration was reported by others [68]. Melanomas harboring NRAS mutations have shown greater mitotic rates than BRAF mutant melanomas [63,68].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 95%
“…The incidence of the NRAS mutation according to tumor site was highest in the extremities (25%), followed by the face or scalp (18%) and trunk (18%) [55,61,63]. NRAS mutations have also been found in conjunctival melanomas (18% frequency) [63], sinonasal melanomas (22%) [65], esophageal melanomas (37.5%), including mutations in exon 1, which is a rare mutation site for cutaneous melanoma [66]. Interestingly, melanoma of unknown primary sites showed NRAS mutations in 32% of cases associated with high somatic mutation rates, high ratios of C>T/G>A transitions, and a 45% of BRAF mutations, collectively indicating a mutation profile consistent with cutaneous sun-exposed melanomas [67].…”
Section: Nras In Melanocytic Cell Neoplasmsmentioning
confidence: 99%
“…6,7 Targeted therapies (vemurafenib and imatinib) available for patients harbouring BRAF, 8 NRAS, 9 and KIT 10 mutations have added therapeutic relevance to mutational subtyping of malignant melanoma. Increasing evidence demonstrated that mutational characteristics segregate with currently accepted subtyping based on histology and tumor location: [11][12][13][14][15][16] uveal melanomas present the prototypical case of a melanoma entity with a distinct mutation profile as they typically lack BRAF mutations, 17 but instead frequently display GNAQ or GNA11 mutations. 18,19 Spitzoid melanomas demonstrate a reduced BRAF mutation frequency compared to general melanoma, 11 and mucosal melanomas are frequently KIT mutated but BRAF wild type.…”
mentioning
confidence: 99%